Thermotolerance adaptation to human‐modified habitats occurs in the native range of the invasive ant Wasmannia auropunctata before long‐distance dispersal. (11th March 2013) - Foucaud, Julien; Rey, Olivier; Robert, Stéphanie; Crespin, Laurent; Orivel, Jérôme; Facon, Benoit; Loiseau, Anne; Jourdan, Hervé; Kenne, Martin; Masse, Paul Serge Mbenoun; Tindo, Maurice; Vonshak, Merav; et al.
Abstract Key evolutionary events associated with invasion success are traditionally thought to occur in the introduced, rather than the native range of species. In the invasive ant Wasmannia auropunctata, however, a shift in reproductive system has been demonstrated within the native range, from the sexual non‐dominant populations of natural habitats to the clonal dominant populations of human‐modified habitats. Because abiotic conditions of human‐ modified habitats are hotter and dryer, we performed lab experiments on workers from a set of native and introduced populations, to investigate whether these ecological and genetic transitions were accompanied by a change in thermotolerance and whether such changes occurred before establishment in the introduced range. Thermotolerance levels were higher in native populations from human‐modified habitats than in native populations from natural habitats, but were similar in native and introduced populations from human‐modified habitats. Differences in thermotolerance could not be accounted for by differences in body size. A scenario based on local adaptation in the native range before introduction in remote areas represents the most parsimonious hypothesis to account for the observed phenotypic pattern. These findings highlight the importance of human land use in explaining major contemporary evolutionary changes.